Pleural mesothelioma in doll manufacture: possible asbestos exposure - Barbieri, Pietro Gino; Somigliana, Anna Benedetta; Lombardi, Sandra; Festa, Roberto; Girelli, Roberto; Sarnico, Michela (La Medicina del Lavoro, 2017)
Background: The occurrence of malignant mesothelioma is almost always causally associated to asbestos exposure but, considering women occurrences, this association is often difficult to demonstrate and consequently the asbestos exposure is defined as ‘unknown’. Objectives: To describe the working activity and to give occupational asbestos exposure probability estimation related to an uncommon and poorly investigated productive sector: doll manufacture. Methods: From the Province of Brescia Mesothelioma Registry, established in 1993 on population-based criteria, we have extracted the certified mesothelioma diagnosis cases, related to patients who were employed for some time in doll manufacture. Results: Among the 757 total cases of malignant mesothelioma registered and studied up to 2016, we found 3 cases of pleural epithelial mesothelioma histologically diagnosed in young women who had worked in two doll manufacturing companies and whose asbestos exposure had been initially defined as ‘unknown’, because an environmental, family or extra-professional asbestos exposure was considered unlikely. However, the judicial autopsy performed on one of the 3 women had allowed examining lung tissue samples with Scanning Electron Microscopy. This technique showed a concentration of amphiboles fibers of about 12,000,000 per gram of dry lung tissue, with a consequent re-classification of asbestos exposure from ‘unknown’ to ‘occupational certified’. Discussion: Mesotheliomas in women with no apparent occupational asbestos exposure are normally referred to life or family environmental exposure. Moreover, it is known that occupational asbestos exposure in women is difficult to recognize. Previously, only one publication had reported two cases of mesothelioma in cloth doll manufacture. The occurrence of two mesothelioma cases in the same company out of the three here presented was suggesting an occupational exposure. The finding of a high amphibole fibers lung concentration confirmed the previous hypothesis, despite the impossibility to determine the circumstances with good evidence. Conclusion: The three cases of mesothelioma in doll production workers suggest that also in this restricted manufacturing sector had occurred an occupational asbestos exposure, which is up to now unknown and isn’t due only to the use of sewing or ironing machines. The lung asbestos fibers burden analysis is confirmed to be a decisive factor in the assessment of mesothelioma cases with ‘unknown’ exposure.